2008
DOI: 10.1113/expphysiol.2008.043877
|View full text |Cite
|
Sign up to set email alerts
|

Myonuclear domain size and myosin isoform expression in muscle fibres from mammals representing a 100 000‐fold difference in body size

Abstract: This comparative study of myonuclear domain (MND) size in mammalian species representing a 100 000-fold difference in body mass, ranging from 25 g to 2500 kg, was undertaken to improve our understanding of myonuclear organization in skeletal muscle fibres. Myonuclear domain size was calculated from three-dimensional reconstructions in a total of 235 single muscle fibre segments at a fixed sarcomere length. Irrespective of species, the largest MND size was observed in muscle fibres expressing fast myosin heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 51 publications
(69 reference statements)
5
65
0
1
Order By: Relevance
“…36 -37 Because it is highly dependent on muscle fiber type, independently of species, the increased myonuclear domain could be in close relationship with the notable increase in ␣-MHC observed in ALA hamster muscles. 38 In addition to biochemical and morphological effects, the different membrane PUFAs molar percentage was associated with a lower inflammatory potential mainly driven through resolvins and protectins, 11,16,39 -40 but also caused by 3 EPA competitive inhibition of the cascade of AA, the precursor of 6 derived proinflammatory eicosanoids (eg, TXA2, PGD2, PGE2, LTA1). EPA is an important anti-inflammatory reagent, 11 and beneficial effects have been obtained in primary muscle cell culture from Duchenne muscular dystrophy patients using inhibitors of the AA cascade.…”
Section: Discussionmentioning
confidence: 99%
“…36 -37 Because it is highly dependent on muscle fiber type, independently of species, the increased myonuclear domain could be in close relationship with the notable increase in ␣-MHC observed in ALA hamster muscles. 38 In addition to biochemical and morphological effects, the different membrane PUFAs molar percentage was associated with a lower inflammatory potential mainly driven through resolvins and protectins, 11,16,39 -40 but also caused by 3 EPA competitive inhibition of the cascade of AA, the precursor of 6 derived proinflammatory eicosanoids (eg, TXA2, PGD2, PGE2, LTA1). EPA is an important anti-inflammatory reagent, 11 and beneficial effects have been obtained in primary muscle cell culture from Duchenne muscular dystrophy patients using inhibitors of the AA cascade.…”
Section: Discussionmentioning
confidence: 99%
“…This is in striking contrast to the 27-fold increase in mean CSA observed in fibers from the smallest and largest black sea bass in the present study. Recent studies have shown that MND size does vary with hypertrophic growth, as well as with muscle atrophy (Allen et al, 1995;Allen et al, 1996;Ohira et al, 1999;Ohira et al, 2001;Rosser et al, 2002;Wada et al, 2003;Bruusgaard et al, 2006;Bruusgaard and Gundersen, 2008;Gundersen and Bruusgaard, 2008;Liu et al, 2008). Rosser et al found that MND size increased during development in chick muscle, which undergoes a relatively large increase in fiber size (~14-fold increase in CSA) during muscle growth (Rosser et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Fiber ends (adjacent to myosepta) and obviously damaged areas of muscle were also excluded from analysis. These above criteria were used to differentiate SS nuclei from satellite cells despite the fact that satellite cells have been reported to represent only 1-5% of all myonuclei (Edgerton and Roy, 1991;Rosser et al, 2002;Liu et al, 2008). Furthermore, Battram and Johnston found that satellite cells were extremely rare in muscle from an Antarctic teleost fish (Notothenia neglecta), suggesting that this may not be a major source of error in fish muscle (Battram and Johnston, 1991).…”
Section: Imaging and Measurementsmentioning
confidence: 99%
“…Thus, higher levels of nuclear gene transcripts (per g tissue) can arise even if there are no differences in gene expression per se. There is a strong relationship between myonuclear domain size and body mass in both fast twitch and slow twitch mammalian muscle fibers (26). In this study on rodents, we found that only TA showed significant negative scaling of mitochondrial enzymes (per g) and positive scaling of glycolytic enzymes (per g), with little effect when myonuclear domain was considered.…”
Section: Scaling Of Metabolic Enzyme Activitiesmentioning
confidence: 66%